Mechanisms of transforming growth factor-β activation in airway smooth muscle cells and its role in asthma - Tatler, Amanda Louise (2010)
Asthma is a chronic inflammatory disease of the airways characterised by airway hyper-responsiveness (AHR), inflammation of the airways and reversible airway obstruction. Airway remodelling is a feature of asthma, especially in cases of severe and fatal asthma, and includes structural changes such as increased airway smooth muscle (ASM) mass, mucous gland hyperplasia, subepithelial fibrosis and angiogenesis. TGF-β is a pleiotropic cytokine that has been implicated in the development of many of these changes. However, TGF-β is released from cells in a latent complex, associated with its pro-peptide the latency associated peptide (LAP). Extracellular activation of latent TGF-β is the rate limiting step in TGF-β bioavailability. Although TGF-β activation has been investigated in airway epithelial cells, to date, no studies have investigated TGF-β activation by airway smooth muscle cells. The hypothesis of this thesis is therefore that human airway smooth muscle cells can activate TGF-β in vitro.